Symbiotic integration of human activities in cyber-physical systems - Fantini, Paola (2020)
Human integration in cyber-physical systems (CPS) is playing a crucial role in the era of the digital transformation, notably because humans are seen as the most ﬂexible driver in an automated system. Two main reference models for human activities in production systems are usually considered, namely Human-in-the-Loop (HitL) and Human-in-the-Mesh (HitM), which present diﬀerent requirements and challenges. This paper aims to overview the diﬀerent activities related to the human integration in CPS, particularly discussing the requirements that can be found in HitL and HitM models for the diﬀerent phases of the decision-making process, namely detect, determine, develop and describe; and analyzing the technologies and computational tools to support these human activities. The human integration in CPS is illustrated through three examples, where humans playing the operator and manager roles are integrated in the PERFoRM and FAR-EDGE ecosystems, covering diﬀerent phases of the decision-making process.